Modelos y diseños estratégicos virtuales para el aprendizaje en el desarrollo educativo en niños con trastorno del espectro autista. (2023)
The Information and Communication Technologies (ICT) are resources that have encompassed a broader scope and expansion over the past century up to the present day as modern educational tactics. These tools enable self-learning and the collective construction of knowledge, contributing to better experiences and more meaningful learning for children with Autism Spectrum Disorder (ASD). Methodology: The literature review emerges from a collection of various scientific research studies centered aroundeducation in children with autism, which allows us to develop specific models and strategic designs through the use of ICT. Results: We utilized a total of 10 articles from the period 2014 to 2022, primarily from Colombia, Ecuador, and Spain. The following search engines and databases were considered: Google Scholar, as well as Redalyc, Scielo, and Dialnet. Conclusion: Taking into account recent events, the importance of using and implementing ICT in the teaching and learning process for students with specific educational needs stands out.